ANALISIS PENGEMBANGAN USAHA JS HIDROPONIK DI KELURAHAN JAKASAMPURNA-BEKASI - Mylanggie, Fazarudin Noor; Ismarani, Ismarani; Ardisela, Dawud (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2024)
JS Hidroponik is a Farmer Group which operates in the field of hydroponic vegetable production located in Jakasampurna Urban Village, West Bekasi Sub-District, Bekasi City. This research aims to determine: (1) internal and external environmental factors that influence the development strategy at JS Hydroponics and (2) look for alternatives and determine priorities for development strategies that are in accordance with JS Hydroponics. Data analysis consists of descriptive methods, while quantitative analysis uses tools, namely the IFE, EFE, IE, SWOT and QSPM matrices. The main strength is quality products and production standards. The main weakness is having limited land and limited capital. The main opportunity is increasing public awareness of healthy living and having business partners. The main threats are pests and diseases, weather changes and nearby competitors. An alternative strategy based on the IE matrix is that JS Hydroponics is in cell I, which means the business is still at the growth and build stage, in line with the QSPM results, namely a strategy to expand marketing.